Aplikasi Pemberitahuan Penggajian dan Pemberian Rekomendasi Pinjaman dengan Metode SAW (Studi Kasus: Rutan Klas 1 Bandung) - Nisa Hanum Harani; Woro Isti Rahayu; Farhan Maulana (Jurnal Manajemen Informatika (JAMIKA), 2020)
The development of increasingly advanced technology has made several things begin to interfere with technology. It is undeniable that at present anything must be related to technology because it is effective and efficient. One of them is the process of disseminating information that is already using the internet to facilitate the dissemination activities. In one of the state agencies, namely Rutan Klas 1 Bandung, especially the finance department, the dissemination of information is needed, especially salary notifications through salary slips which are still manual and consumes paper and ink. In addition, one of the other problems is the provision of loans to employees who sometimes have monthly payment installments greater than the salary received, this is the lack of careful financial staff in recommending a list of loans. To solve this problem, making an application for sending pay slips via e-mail and applying the SAW (Simple Additive Weighting) method to provide the best recommendations for choosing a loan that avoids human error data. So after testing the application, payroll information dissemination via e-mail works well and the SAW method used also provides the best recommendations and eliminates loan data that is impossible for the employee to borrow.